2020
DOI: 10.2305/iucn.ch.2020.patrs.4.en
|View full text |Cite
|
Sign up to set email alerts
|

Protected Areas Benefits Assessment Tool + (PA-BAT+): A tool to assess local stakeholder perceptions of the flow of benefits from protected areas

Abstract: IUCN World Commission on Protected Areas (WCPA) IUCN's World Commission on Protected Areas is the world's premier network of protected area expertise. It is administered by IUCN's Programme on Protected Areas and has over 2,500 members, spanning 140 countries. WCPA helps governments and others plan protected areas and integrate them into all sectors by providing strategic advice to policymakers; by strengthening capacity and investment in protected areas; and by convening the diverse constituency of protected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…To assess non-economic, economic, potentially noneconomic, and potentially economic values research was conducted using the PA-BAT + methodology (Ivanić et al, 2020). The assessment of the value of PAs was performed collected the data by questionnaires for five groups of stakeholders: local population; public sector (managers); government; civil society organizations (CSO); scientists/ experts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess non-economic, economic, potentially noneconomic, and potentially economic values research was conducted using the PA-BAT + methodology (Ivanić et al, 2020). The assessment of the value of PAs was performed collected the data by questionnaires for five groups of stakeholders: local population; public sector (managers); government; civil society organizations (CSO); scientists/ experts.…”
Section: Methodsmentioning
confidence: 99%
“…Mapping the values of PAs, greater participation of decision-makers, and finally changes in public policies and the development of economic models that include natural resources in their development plans are significant but also long-term processes (Trzyna, 2014;Cumming, 2016;Ten Brink et al, 2016;Chen et al, 2020). IUCN has established the Protected Areas Benefits Assessment Tool+ (PA-BAT+) (Ivanić et al, 2020), which provides initial information on how different stakeholders view the current state and potential values of PAs, which can help integrate natural resources and services provided by ecosystems in development plans. Such a tool makes it possible to identify the main factors relevant to the PAs and the country's development policy, the flow of economic benefits, and the need for strategies that will enable the return of income to local people and PAs.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al [23] identified six categories of social impacts that can help in this direction. However, no widely accepted tool for social impact assessment currently exists, apart from some preliminary attempts including the PA-BAT tool [115] and SAPA [116]. The categories identified in Section 3.2 provide a detailed review of the different impacts that need to be included in an in-depth assessment.…”
Section: Stage 1: Map the Governance And Management System Characteri...mentioning
confidence: 99%
“…Although many tools and approaches for assessing NCP have been proposed (e.g., measuring biological carbon storage and sequestration, crop pollination), indicators derived from such assessments have rarely been included in protected area effectiveness evaluations. Encouragingly, the new IUCN Protected Area Benefits Assessment Tool+ (PA-BAT+) aims at collating and assessing information on local stakeholders’ perceptions on the benefits of protected areas (Ivanić et al 2020 ), which could complement quantitative approaches in assessing NCP. However, following the NCP concept, PA-BAT+ should furthermore, expand to also entail the negative impacts of protected areas on local stakeholders.…”
Section: A Social–ecological Framework For Evaluating Protected Area ...mentioning
confidence: 99%